English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

9 answers

3(-2 - 3x) = -9x - 4
3(-2) - 3*3x = -9x - 4
-6 - 9x = -9x - 4
-6 - 9x + 9x + 4 = 0
-2 = 0

You must have typed the problem incorrectly!

2006-10-18 08:27:44 · answer #1 · answered by psbhowmick 6 · 3 0

First Method : Take the rule of multiplying the brackets first and then subtract the values always follow the division first then the multiplication and then the addtion and subtraction so as per me this first method shud work.

3*(-2) - 3(-3x)= -9x -4
-6 +9x +4 = -9x
-2 = -9x -9x
-2 = -18x
2=18x
divide the whole expresion by 18
2/18=18x/18
2/18=x
thus x = 2/18


all others have shown u this problem as the following : Second Method

3(-2) - 3(3x) = -9x -4
-6 -9x = -9x -4
-9x = -9x -4 +6
-9x = -9x +2
and since -9x and -9x get nullified
0=2 which is absurd
so for this way of solving the problem all got 0 =2 since 0 cannot b equal to 2 the expression is false is the answer u can either check ur expression

if this was the right expression then ur answer shud b equal to 2/18 which I've explained u by the first method :)

Try to divide the whole expression by 3 and again u get 0=2 so The expression is false...

2006-10-18 09:02:10 · answer #2 · answered by kittana 6 · 0 0

3(-2-3x)=-9x-4

Step 1 (Use the distributive property on the left side)
-6 - 9x = -9x - 4

Step 2 (Add 9x to both sides)

-6 - 9x = -9x - 4
+9x +9x
-------------------------
-6 = -4 (this is a false statement)

So this problem has no solution.

Answer: No solution

2006-10-18 08:57:21 · answer #3 · answered by ONE_QT_PY 2 · 0 0

3(-2-3x) = -9x - 4
Distribute the 3
-6 - 9x = -9x - 4
Add 9x to each side
-6 = -4
Since this statement is false, it means there is no solution.
Answer: No solution

2006-10-18 08:29:39 · answer #4 · answered by MsMath 7 · 0 0

3(-2-3x)=-9x-4

Appply distributive rule to left side

-6 - 9x = - 9x - 4

add 6 to both sides, add 9x to both sides

0 = 2 ????????????????

You posted a bogus example - try again.

2006-10-18 08:30:10 · answer #5 · answered by Anonymous · 1 0

Yes, I can. Can you?

Hint: use distributive property to multiply out the 3(-2-3x) to get:

3(-2) - 3(3x) = -6-9x

Hope that helps get you started!

2006-10-18 08:28:40 · answer #6 · answered by I ♥ AUG 6 · 0 0

first you use the distributive property which comes to
-6 - 9x= -9x -4
then you use the addition property which comes to
-6 -9x + 9x = -4
then you use the addition property which comes to
-9x + 9x = 2
then you use the addition property which comes to..... You figure it out from there.

2006-10-18 08:32:32 · answer #7 · answered by Winter M 1 · 0 0

3(-2-3x)=-9x-4
-6-9x=-9x-4
-9x+9x=-4+6
0=2
its inconsistent for there is no solution

2006-10-18 21:33:24 · answer #8 · answered by anne frances s 1 · 0 0

HE didnt post a "bogus example", the answer IS 'No Solution' because -2=0, and obviously since it doesnt, it just "No Solution".

2006-10-18 08:32:12 · answer #9 · answered by Bobby B 3 · 0 0

fedest.com, questions and answers